تأثير تصريف وحدة معالجة مياه الصرف الصحي في بعض الخصائص الفيزيائية و الكيميائية و الجرثومية لمياه نهر الفرات قرب مركز مدينة الناصرية – جنوب العراق - الغالبي, بشرى علي (University of Thi-Qar Journal of Science, 2013)
The present study deal with measurement some physical ,chemical and bacteriological properties ofEuphrates river such as(DO,BOD,TOC ,Cd,Cu,Ni,Pb,Zn ,Fecal coli bacteria) . samples collected from fivestations in Euphrates river and wastewater treatment station near Al-Nassyria city center - southIraq,during the period Autumn 2011 to summer 2012 .The result showed that dissolved oxygen valueranged between (0.06-10.75) ml/L, BOD5 were recorded (1.8-108) ml/L, TOC were recorded (0.95-4.99)%,total number of Fecal coli bacteria were recorded(350-10)cell/100ml .This study showed that theconcentrations averages of Cd, Cu, Ni, Pb and Zn in dissolved phase in water were (0.23,0.72,2.05,2 and5.1)/L,While there concentration in particulate phase were (4.08,18.8,11.3,22.07and 34.9)µg/g dryweight.The concentration in sediments were(3.18,21.4,37.5,68.8and 31.9)µg/g dry weight.some of thesecharacteristics (dissolved oxygen ,biological oxygen demand ,fecal coli bacteria) were overcome thestandard of the Iraqi rivers maintenance system , and the Iraqi and WHO standard for drinking,conclusion ofthis study that Wastewater treatment plant didn't decrease from pollution of pollutants in this study.